Eksistensi Pemasaran Syariaah dalam Ekosistem Bisnis Hotel di Masa Pandemi Covid-19 - Amalia Yustika; Ana Toni Roby Candra Yudha; Sugiyanto Sugiyanto (Nomicpedia: Journal of Economics and Business Innovation, 2023)
The study aims to determine sharia marketing strategies and the obstacles encountered in increasing the number of visitors during the COVID-19 pandemic at the Radho Syariah Malang Hotel. The research method conducted at the Radho Syariah Hotel Malang uses a qualitative descriptive method with primary data obtained through field surveys of hotel owners and tourists as well as secondary data from the official websites of hotels and travel agents. Data collection techniques were carried out through observation, interviews, and recording. The results obtained in this study are the Sharia Marketing Strategy implemented by Hotel Radho Syariah in the form of a promotional strategy by giving customers a 25% discount and a 20% discount only for special customers such as Islamic boarding school children to increase the number of visitors during the COVID-19 pandemic. In addition, there were obstacles encountered in increasing the number of visitors during the COVID-19 pandemic, including internal obstacles in the form of a lack of cohesiveness between the F&B Kitchen and Engine marketing divisions, suddenly jammed water pumps, troubled WiFi, and external obstacles in the form of too many non-sharia-based hotel competitors. The recommendations that can be used as input to the Radho Syariah Hotel Management are expected to further increase creativity and innovation in the marketing of hotel services offered to the public and in accordance with the principles of sharia marketing strategies, to increase sales to the right markets and achieve trust and loyalty. customer